2023
DOI: 10.3390/ijms24043964
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization and Functional Analysis of Glucose Regulated Protein 78 from the Silkworm Bombyx mori

Abstract: The glucose regulated protein (GRP78) is an important chaperone for various environmental and physiological stimulations. Despite the importance of GRP78 in cell survival and tumor progression, the information regarding GRP78 in silkworm Bombyx mori L. is poorly explored. We previously identified that GRP78 expression was significantly upregulated in the silkworm Nd mutation proteome database. Herein, we characterized the GRP78 protein from silkworm B. mori (hereafter, BmGRP78). The identified BmGRP78 protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Notably, Hsc70-4 demonstrated an up-regulated expression in the fat body, a phenomenon associated with Bombyx mori nucleopolyhedrovirus (BmNPV) infection, as reported previously ( 59–61 ). In our previous research, we observed an induction in the translational level of BmGRP78 (also known as Hsc70-3 ) and its translocation into the cell nucleus following Hg exposure ( 62 ). These results demonstrated that these HSP proteins may be functionally related to Hg exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, Hsc70-4 demonstrated an up-regulated expression in the fat body, a phenomenon associated with Bombyx mori nucleopolyhedrovirus (BmNPV) infection, as reported previously ( 59–61 ). In our previous research, we observed an induction in the translational level of BmGRP78 (also known as Hsc70-3 ) and its translocation into the cell nucleus following Hg exposure ( 62 ). These results demonstrated that these HSP proteins may be functionally related to Hg exposure.…”
Section: Discussionmentioning
confidence: 98%